Evaluation of Heat Rejection Systems for PL-3 - Thurnau, C. J. (Alco Products (Firm), 1962)
An investigation was made of heat rejection systems for use in the PL-3 nuclear power plant, designed for placement at Byrd Station, Antarctica. It was concluded that the glycol-coupled surface condenser and air blast cooler combination appears to be suited for PL-3 plant requirements and operating conditions. (auth)